Quick-drying waterborne epoxy coating and preparation method thereof
By combining modified cyclotetrasiloxane, functionalized polysiloxane and modified graphene, quick-drying water-based epoxy coatings are prepared, which solves the brittleness and corrosion resistance of existing water-based epoxy coatings. The problem of this paper achieves good anti-corrosion, self-healing, flame retardant, antibacterial and wear resistance of the paint.
Patent Information
- Application Number
- CN202411655406.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing water-based epoxy coatings are brittle and have weak corrosion resistance, making it difficult to achieve excellent levels of mechanical properties and corrosion resistance.
Quick-drying water-based epoxy coatings are prepared by combining materials such as modified cyclotetrasiloxane, functionalized polysiloxane and modified graphene. The coating introduces rich double bonds and amino groups during the reaction process to form a dual curing system, and improves corrosion resistance and flame retardant properties through the addition of graphene oxide.
It has achieved good anti-corrosion performance, self-repairing performance, flame retardant performance, antibacterial performance and wear resistance of fast-drying water-based epoxy coatings, significantly improving its mechanical properties and anti-corrosion performance.
Abstract
Description
Technical Field
[0001] The invention relates to the field of coatings, in particular to a quick-drying water-based epoxy coating and a preparation method thereof. Background Art
[0002] Epoxy resin is a polymer with aliphatic and aromatic groups as basic structures and two or more epoxy groups in the molecular chain. Epoxy resin has good corrosion resistance and mechanical properties and is widely used in the field of coatings. The volatile organic compounds contained in the common solvent-based epoxy coatings on the market can cause great harm to human health and the environment. Therefore, reducing the emission of volatile organic compounds is the main task of the current coatings industry.
[0003] Waterborne epoxy coatings do not contain volatile organic compounds and have the advantages of being green, environmentally friendly, non-toxic and harmless. However, waterborne epoxy coatings are brittle and have weaker corrosion resistance than solvent-based epoxy coatings, so they need to be modified to obtain composite coatings with excellent mechanical properties and anti-corrosion properties. The quick-drying waterborne epoxy coating prepared by the present invention has good anti-corrosion properties, self-repairing properties, flame retardant properties, antibacterial properties and wear resistance, and has broad market prospects. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a quick-drying water-based epoxy coating to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] The invention discloses a quick-drying waterborne epoxy coating. The quick-drying waterborne epoxy coating comprises the following steps: reacting modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and quaternized silane to obtain functionalized polysiloxane; reacting graphene oxide with ethylenediamine and allylphosphine dichloride to obtain modified graphene; preparing component A from modified graphene, functionalized polysiloxane, defoamer, azobisisobutyronitrile and deionized water; and mixing component A and component B uniformly to obtain the quick-drying waterborne epoxy coating with waterborne epoxy emulsion as component B.
[0007] A method for preparing a quick-drying waterborne epoxy coating comprises the following preparation steps:
[0008] (1) Tetramethylcyclotetrasiloxane, 4-(2-allyl)-catechol and chloroplatinic acid were mixed in a mass ratio of 1:
[0009] (0.3-0.7): (0.002-0.004) are mixed, reacted at 80-90°C for 5-7h, cooled to room temperature, and phenolic hydroxyl-modified cyclotetrasiloxane is obtained; phenolic hydroxyl-modified cyclotetrasiloxane and methyl propylene isocyanate are mixed at a mass ratio of 1: (0.6-0.8), stirred at 70-80°C at 100-200r / min for 4-6h to obtain modified cyclotetrasiloxane; N,N-dimethylaminopropyldimethylmethoxysilane and propylene chloride are mixed at a mass ratio of 1: (0.7-0.9), stirred at 80-90°C at 300-500r / min for 6-10h, cooled to room temperature, and quaternized ammonium silane is obtained;
[0010] (2) Modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and tetramethylammonium hydroxide silicon alkoxide are mixed in a mass ratio of 1: (0.5-0.7): (0.5-0.7): (0.01-0.03), nitrogen is passed through for 10-20 min, stirred at 100-200 r / min at 80-90° C. for 2-3 h, quaternary ammonium silane of 0.2-0.4 times the mass of tetramethylcyclotetrasiloxane is added, the temperature is raised to 95-105° C. and stirring is continued for 7-9 h, the temperature is raised to 130-140° C. at 10-20° C. / min and stirring is continued for 40-50 min, and distilled at 0.1-0.3 MPa for 1-2 h to obtain functionalized polysiloxane;
[0011] (3) Graphene oxide and deionized water are mixed at a mass ratio of 1:(190-210), and ultrasonicated for 25-35 min to obtain a graphene oxide suspension. The graphene oxide suspension and ethylenediamine are mixed at a mass ratio of 1:(7-8), and stirred at 65-75° C. and a speed of 60-80 r / min for 1.5-2.5 h. The solid product is centrifuged and washed with deionized water for 3-5 times, and freeze-dried for 46-50 h to obtain primary modified graphene. The primary modified graphene oxide, ethylenediamine, and allyl dichloride are mixed. Phosphine, triethylamine and toluene are mixed in a mass ratio of 1: (0.4-0.6): (0.6-0.8): (0.1-0.2): (20-30), stirred at 200-400 r / min for 2-4 hours at 0-5°C, filtered, washed the filter residue with deionized water for 3-5 times, immersed in a 20%-30% mass concentration ethylenediamine ethanol solution for 1-3 hours, filtered, washed the filter residue with deionized water and anhydrous ethanol for 3-5 times respectively, and freeze-dried for 46-50 hours to obtain modified graphene;
[0012] (4) diallyl bisphenol A diglycidyl ether and polyethylene glycol are mixed in a mass ratio of 1:(5-15) and heated at 100° C. for 30 min, and the temperature is raised to 175-185° C., potassium persulfate is added in an amount of 0.0002-0.0004 times the mass of diallyl bisphenol A diglycidyl ether, and the mixture is stirred at 250-350 r / min for 3-5 h to obtain an emulsifier; diallyl bisphenol A diglycidyl ether, OP-10, and an emulsifier are mixed in a mass ratio of 1:(0.02-0.04):(0.06-0.08), and the mixture is stirred at 4500-5500 r / min for 5-15 min at 55-65° C., and deionized water is added dropwise at a rate of 160 ml / min. The addition of the dropwise addition is stopped when the solid content reaches 50%-60%, to obtain an aqueous epoxy emulsion;
[0013] (5) Weigh 1 to 2 parts of modified graphene, 0.025 to 0.035 parts of wetting and dispersing agent, 75 to 85 parts of functionalized polysiloxane, 0.025 to 0.035 parts of defoaming agent, 0.003 to 0.005 parts of azobisisobutyronitrile and 90 to 110 parts of deionized water and mix them evenly to obtain component A; the water-based epoxy emulsion is component B; and component A and component B are mixed at a mass ratio of 1:(0.8 to 1) to obtain a quick-drying water-based epoxy coating.
[0014] As an optimization, the graphene oxide described in step (3) is graphene oxide with a purity of 96%, which is purchased from Suzhou Carbon Graphene Technology Co., Ltd.
[0015] As an optimization, the polyethylene glycol described in step (4) is polyethylene glycol with an average molecular weight of 4000.
[0016] As an optimization, the wetting and dispersing agent described in step (5) is a YL-190 type dispersant purchased from Nantong Yongle Chemical Co., Ltd.; the defoaming agent is an AKN-3386 type defoaming agent purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0018] When preparing the quick-drying waterborne epoxy coating, the invention comprises the following steps: tetramethylcyclotetrasiloxane is reacted with 4-(2-allyl)-catechol and then reacted with methyl propylene isocyanate to obtain modified cyclotetrasiloxane; N,N-dimethylaminopropyldimethylmethoxysilane is reacted with allyl chloride to obtain quaternized silane; modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and quaternized silane are reacted to obtain functionalized polysiloxane; graphene oxide is reacted with ethylenediamine and allylphosphine dichloride to obtain modified graphene; modified graphene, functionalized polysiloxane, defoamer, azobisisobutyronitrile and deionized water are used to obtain component A; waterborne epoxy emulsion is used as component B; component A and component B are mixed to obtain the quick-drying waterborne epoxy coating.
[0019] Firstly, 4-(2-allyl)-catechol, methyl methacrylate isocyanate and allyl chloride introduce abundant double bonds on the functionalized polysiloxane, which can cross-link with the double bonds on diallyl bisphenol A diglycidyl ether and modified graphene under the action of azobisisobutyronitrile, thereby increasing the cross-linking density of the quick-drying waterborne epoxy coating and thus improving its wear resistance; 3-aminopropylmethyldimethoxysilane makes the functionalized polysiloxane have a large number of amino groups, which can react with the epoxy groups on diallyl bisphenol A diglycidyl ether to effectively cure the epoxy resin and form a dual curing system with the cross-linking curing of the double bonds; N,N-dimethylaminopropyl dimethyl Oxysilane reacts with allyl chloride to prepare quaternized silane. The presence of quaternary ammonium salt cations not only improves the antibacterial properties of the fast-drying waterborne epoxy coating, but also makes the functionalized polysiloxane have good hydrophilicity and can be well dispersed in water. The phenolic hydroxyl group on 4-(2-allyl)-catechol can block methyl acrylate isocyanate. After the fast-drying waterborne epoxy coating is applied to the substrate to form a coating, heating can deblock the isocyanate. The isocyanate group reacts with the epoxy group to repair the coating surface, and the polyphenols on the 4-(2-allyl)-catechol are released, which has an anti-aging effect, thereby improving the anti-aging performance of the fast-drying waterborne epoxy coating.
[0020] Secondly, graphene oxide is reacted with ethylenediamine and allylphosphine dichloride to prepare modified graphene, and phosphorus is introduced on the graphene, which promotes the formation of a dense carbon layer on the surface of the coating. The dense carbon layer can block the transfer of heat and oxygen, reduce the combustion inside the material, and thus improve the flame retardant properties of the quick-drying water-based epoxy coating; graphene oxide can play a barrier role in the combustion process, preventing the escape of combustible gases and heat, thereby effectively improving the flame retardant properties of the quick-drying water-based epoxy coating, and graphene oxide as a flaky structure can effectively block the propagation of water and sodium salt ions, thereby improving the anti-corrosion performance of the quick-drying water-based epoxy coating. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] Embodiment 1:
[0023] A method for preparing a quick-drying waterborne epoxy coating comprises the following preparation steps:
[0024] (1) Tetramethylcyclotetrasiloxane, 4-(2-allyl)-catechol, and chloroplatinic acid were mixed in a mass ratio of 1:0.3:0.002, reacted at 80°C for 5 hours, and cooled to room temperature to obtain phenolic hydroxyl-modified cyclotetrasiloxane; phenolic hydroxyl-modified cyclotetrasiloxane and methyl propylene isocyanate were mixed in a mass ratio of 1:0.6, stirred at 70°C at 100 r / min for 4 hours to obtain modified cyclotetrasiloxane; N,N-dimethylaminopropyldimethylmethoxysilane and propylene chloride were mixed in a mass ratio of 1:0.7, stirred at 80°C at 300 r / min for 6 hours, and cooled to room temperature to obtain quaternary ammonium silane;
[0025] (2) Modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:0.5:0.5:0.01, nitrogen was passed for 10 minutes, and the mixture was stirred at 80°C and 100 r / min for 2 hours. A quaternary ammonium silane with a mass of 0.2 times that of tetramethylcyclotetrasiloxane was added, the temperature was raised to 95°C and stirring was continued for 7 hours, the temperature was raised to 130°C at 10°C / min and stirring was continued for 40 minutes, and the mixture was distilled at 0.1 MPa for 1 hour to obtain a functionalized polysiloxane.
[0026] (3) Graphene oxide and deionized water were mixed at a mass ratio of 1:190, and ultrasonicated for 25 minutes to obtain a graphene oxide suspension. The graphene oxide suspension and ethylenediamine were mixed at a mass ratio of 1:7, stirred at 65°C at a speed of 60 r / min for 1.5 hours, and the solid product was centrifuged to obtain the solid product, which was washed three times with deionized water and freeze-dried for 46 hours to obtain the primary modified graphene; the primary modified graphene oxide, ethylenediamine, allylphosphine dichloride, triethylamine, and toluene were mixed at a mass ratio of 1:0.4:0.6:0.1:20, stirred at 200 r / min at 0°C for 2 hours, filtered, and the filter residue was washed three times with deionized water, and then immersed in a 20% mass concentration ethylenediamine ethanol solution for 1 hour, filtered, and the filter residue was washed three times with deionized water and anhydrous ethanol, respectively, and freeze-dried for 46 hours to obtain modified graphene;
[0027] (4) Diallyl bisphenol A diglycidyl ether and polyethylene glycol were mixed in a mass ratio of 1:5 and heated at 100°C for 30 minutes, and the temperature was raised to 175°C, potassium persulfate was added in an amount of 0.0002 times the mass of diallyl bisphenol A diglycidyl ether, and stirred at 250 r / min for 3 hours to obtain an emulsifier; diallyl bisphenol A diglycidyl ether, OP-10, and emulsifier were mixed in a mass ratio of 1:0.02:0.06, stirred at 4500 r / min for 5 minutes at 55°C, and deionized water was added dropwise at a rate of 160 ml / min. The addition was stopped when the solid content reached 50%, and a water-based epoxy emulsion was obtained;
[0028] (5) Weigh 1 part of modified graphene, 0.025 parts of wetting and dispersing agent, 75 parts of functionalized polysiloxane, 0.025 parts of defoaming agent, 0.003 parts of azobisisobutyronitrile and 90 parts of deionized water and mix them evenly to obtain component A; the water-based epoxy emulsion is component B; and component A and component B are mixed at a mass ratio of 1:0.8 to obtain a quick-drying water-based epoxy coating.
[0029] Embodiment 2:
[0030] A method for preparing a quick-drying waterborne epoxy coating comprises the following preparation steps:
[0031] (1) Tetramethylcyclotetrasiloxane, 4-(2-allyl)-catechol, and chloroplatinic acid were mixed in a mass ratio of 1:0.5:0.003, reacted at 85°C for 6 hours, and cooled to room temperature to obtain phenolic hydroxyl-modified cyclotetrasiloxane; phenolic hydroxyl-modified cyclotetrasiloxane and methyl propylene isocyanate were mixed in a mass ratio of 1:0.7, stirred at 75°C at 150 r / min for 5 hours to obtain modified cyclotetrasiloxane; N,N-dimethylaminopropyldimethylmethoxysilane and propylene chloride were mixed in a mass ratio of 1:0.8, stirred at 85°C at 400 r / min for 8 hours, and cooled to room temperature to obtain quaternary ammonium silane;
[0032] (2) Modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:0.6:0.6:0.02, nitrogen was passed for 15 minutes, and the mixture was stirred at 85°C and 150 r / min for 2.5 hours. A quaternary ammonium silane with a mass of 0.3 times that of tetramethylcyclotetrasiloxane was added, the mixture was heated to 100°C and stirred for 8 hours, the mixture was heated to 135°C at 15°C / min and stirred for 45 minutes, and the mixture was distilled at 0.2 MPa for 1.5 hours to obtain a functionalized polysiloxane.
[0033] (3) Graphene oxide and deionized water were mixed at a mass ratio of 1:200, and ultrasonicated for 30 minutes to obtain a graphene oxide suspension. The graphene oxide suspension and ethylenediamine were mixed at a mass ratio of 1:7.5, stirred at 70°C at a speed of 70 r / min for 2 hours, and the solid product was centrifuged to obtain the solid product, which was washed 4 times with deionized water and freeze-dried for 48 hours to obtain the primary modified graphene; the primary modified graphene oxide, ethylenediamine, allylphosphine dichloride, triethylamine, and toluene were mixed at a mass ratio of 1:0.5:0.7:0.15:25, stirred at 2.5°C at 300 r / min for 3 hours, filtered, and the filter residue was washed 4 times with deionized water, and then immersed in a 25% mass concentration ethylenediamine ethanol solution for 2 hours, filtered, and the filter residue was washed 4 times with deionized water and anhydrous ethanol, respectively, and freeze-dried for 48 hours to obtain modified graphene;
[0034] (4) Diallyl bisphenol A diglycidyl ether and polyethylene glycol were mixed in a mass ratio of 1:10 and heated at 100°C for 30 minutes, and then the temperature was raised to 180°C, potassium persulfate was added in an amount of 0.0003 times the mass of diallyl bisphenol A diglycidyl ether, and the mixture was stirred at 300 r / min for 4 hours to obtain an emulsifier; Diallyl bisphenol A diglycidyl ether, OP-10, and emulsifier were mixed in a mass ratio of 1:0.03:0.07, and the mixture was stirred at 5000 r / min for 10 minutes at 60°C, and then deionized water was added dropwise at a rate of 160 ml / min. The addition was stopped when the solid content reached 55%, and a water-based epoxy emulsion was obtained;
[0035] (5) Weigh 1.5 parts of modified graphene, 0.03 parts of wetting and dispersing agent, 80 parts of functionalized polysiloxane, 0.03 parts of defoaming agent, 0.004 parts of azobisisobutyronitrile and 100 parts of deionized water and mix them evenly to obtain component A; the water-based epoxy emulsion is component B; and component A and component B are mixed at a mass ratio of 1:0.9 to obtain a quick-drying water-based epoxy coating.
[0036] Embodiment 3:
[0037] A method for preparing a quick-drying waterborne epoxy coating comprises the following preparation steps:
[0038] (1) Tetramethylcyclotetrasiloxane, 4-(2-allyl)-catechol, and chloroplatinic acid were mixed in a mass ratio of 1:0.7:0.04, reacted at 90°C for 7 hours, and cooled to room temperature to obtain phenolic hydroxyl-modified cyclotetrasiloxane; phenolic hydroxyl-modified cyclotetrasiloxane and methyl propylene isocyanate were mixed in a mass ratio of 1:0.8, stirred at 80°C at 200 r / min for 6 hours to obtain modified cyclotetrasiloxane; N,N-dimethylaminopropyldimethylmethoxysilane and propylene chloride were mixed in a mass ratio of 1:0.9, stirred at 90°C at 500 r / min for 10 hours, and cooled to room temperature to obtain quaternary ammonium silane;
[0039] (2) Modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:0.7:0.7:0.03, nitrogen was passed through for 20 minutes, and the mixture was stirred at 200 r / min at 90°C for 3 hours. A quaternary ammonium silane with a mass of 0.4 times that of tetramethylcyclotetrasiloxane was added, the mixture was heated to 105°C and stirred for 9 hours, the mixture was heated to 140°C at 20°C / min and stirred for 50 minutes, and the mixture was distilled at 0.3 MPa for 2 hours to obtain a functionalized polysiloxane.
[0040] (3) Graphene oxide and deionized water were mixed at a mass ratio of 1:210, and ultrasonicated for 35 minutes to obtain a graphene oxide suspension. The graphene oxide suspension and ethylenediamine were mixed at a mass ratio of 1:8, stirred at 75°C at a speed of 80 r / min for 2.5 hours, and the solid product was centrifuged to obtain the solid product, which was washed 5 times with deionized water and freeze-dried for 50 hours to obtain the primary modified graphene; the primary modified graphene oxide, ethylenediamine, allylphosphine dichloride, triethylamine, and toluene were mixed at a mass ratio of 1:0.6:0.8:0.2:30, stirred at 5°C at 400 r / min for 4 hours, filtered, and the filter residue was washed 5 times with deionized water, and then immersed in a 30% mass concentration ethylenediamine ethanol solution for 3 hours, filtered, and the filter residue was washed 5 times with deionized water and anhydrous ethanol, respectively, and freeze-dried for 50 hours to obtain modified graphene;
[0041] (4) Diallyl bisphenol A diglycidyl ether and polyethylene glycol were mixed in a mass ratio of 1:15 and heated at 100°C for 30 minutes, and then the temperature was raised to 185°C, potassium persulfate was added in an amount of 0.0004 times the mass of diallyl bisphenol A diglycidyl ether, and the mixture was stirred at 350 r / min for 5 hours to obtain an emulsifier; Diallyl bisphenol A diglycidyl ether, OP-10, and emulsifier were mixed in a mass ratio of 1:0.04:0.08, and the mixture was stirred at 5500 r / min for 15 minutes at 65°C, and then deionized water was added dropwise at a rate of 160 ml / min. The addition was stopped when the solid content reached 60%, and a water-based epoxy emulsion was obtained;
[0042] (5) Weigh 2 parts of modified graphene, 0.035 parts of wetting and dispersing agent, 85 parts of functionalized polysiloxane, 0.035 parts of defoaming agent, 0.005 parts of azobisisobutyronitrile and 110 parts of deionized water and mix them evenly to obtain component A; the water-based epoxy emulsion is component B; and component A and component B are mixed in a mass ratio of 1:1 to obtain a quick-drying water-based epoxy coating.
[0043] Comparative Example 1:
[0044] A method for preparing a quick-drying waterborne epoxy coating comprises the following preparation steps:
[0045] (1) Tetramethylcyclotetrasiloxane, 4-(2-allyl)-catechol, and chloroplatinic acid were mixed in a mass ratio of 1:0.5:0.003, reacted at 85°C for 6 hours, and cooled to room temperature to obtain phenolic hydroxyl-modified cyclotetrasiloxane; phenolic hydroxyl-modified cyclotetrasiloxane and methyl propylene isocyanate were mixed in a mass ratio of 1:0.7, stirred at 75°C at 150 r / min for 5 hours to obtain modified cyclotetrasiloxane; N,N-dimethylaminopropyldimethylmethoxysilane and propylene chloride were mixed in a mass ratio of 1:0.8, stirred at 85°C at 400 r / min for 8 hours, and cooled to room temperature to obtain quaternary ammonium silane;
[0046] (2) Modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:0.6:0.6:0.02, nitrogen was passed for 15 minutes, and the mixture was stirred at 85°C and 150 r / min for 2.5 hours. A quaternary ammonium silane with a mass of 0.3 times that of tetramethylcyclotetrasiloxane was added, the mixture was heated to 100°C and stirred for 8 hours, the mixture was heated to 135°C at 15°C / min and stirred for 45 minutes, and the mixture was distilled at 0.2 MPa for 1.5 hours to obtain a functionalized polysiloxane.
[0047] (3) Graphene oxide and deionized water were mixed at a mass ratio of 1:200, and ultrasonicated for 30 minutes to obtain a graphene oxide suspension. The graphene oxide suspension and ethylenediamine were mixed at a mass ratio of 1:7.5, stirred at 70°C and a speed of 70 r / min for 2 hours, and the solid product was centrifuged, washed with deionized water for 4 times, and freeze-dried for 48 hours to obtain primary modified graphene;
[0048] (4) Diallyl bisphenol A diglycidyl ether and polyethylene glycol were mixed in a mass ratio of 1:10 and heated at 100°C for 30 minutes, and then the temperature was raised to 180°C, potassium persulfate was added in an amount of 0.0003 times the mass of diallyl bisphenol A diglycidyl ether, and the mixture was stirred at 300 r / min for 4 hours to obtain an emulsifier; Diallyl bisphenol A diglycidyl ether, OP-10, and emulsifier were mixed in a mass ratio of 1:0.03:0.07, and the mixture was stirred at 5000 r / min for 10 minutes at 60°C, and then deionized water was added dropwise at a rate of 160 ml / min. The addition was stopped when the solid content reached 55%, and a water-based epoxy emulsion was obtained;
[0049] (5) Weigh 1.5 parts of modified graphene, 0.03 parts of wetting and dispersing agent, 80 parts of functionalized polysiloxane, 0.03 parts of defoaming agent, 0.004 parts of azobisisobutyronitrile and 100 parts of deionized water and mix them evenly to obtain component A; the water-based epoxy emulsion is component B; and component A and component B are mixed at a mass ratio of 1:0.9 to obtain a quick-drying water-based epoxy coating.
[0050] Comparative Example 2:
[0051] A method for preparing a quick-drying waterborne epoxy coating comprises the following preparation steps:
[0052] (1) Tetramethylcyclotetrasiloxane, 4-(2-allyl)-catechol, and chloroplatinic acid were mixed in a mass ratio of 1:0.5:0.003, reacted at 85°C for 6 hours, and cooled to room temperature to obtain phenolic hydroxyl-modified cyclotetrasiloxane; phenolic hydroxyl-modified cyclotetrasiloxane and methyl propylene isocyanate were mixed in a mass ratio of 1:0.7, stirred at 75°C at 150 r / min for 5 hours to obtain modified cyclotetrasiloxane; N,N-dimethylaminopropyldimethylmethoxysilane and propylene chloride were mixed in a mass ratio of 1:0.8, stirred at 85°C at 400 r / min for 8 hours, and cooled to room temperature to obtain quaternary ammonium silane;
[0053] (2) Modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:0.6:0.6:0.02, nitrogen was passed for 15 minutes, and the mixture was stirred at 85°C and 150 r / min for 2.5 hours. A quaternary ammonium silane with a mass of 0.3 times that of tetramethylcyclotetrasiloxane was added, the mixture was heated to 100°C and stirred for 8 hours, the mixture was heated to 135°C at 15°C / min and stirred for 45 minutes, and the mixture was distilled at 0.2 MPa for 1.5 hours to obtain a functionalized polysiloxane.
[0054] (3) Diallyl bisphenol A diglycidyl ether and polyethylene glycol were mixed in a mass ratio of 1:10 and heated at 100°C for 30 minutes, and the temperature was raised to 180°C, potassium persulfate was added in an amount of 0.0003 times the mass of diallyl bisphenol A diglycidyl ether, and stirred at 300 r / min for 4 hours to obtain an emulsifier; Diallyl bisphenol A diglycidyl ether, OP-10, and emulsifier were mixed in a mass ratio of 1:0.03:0.07, stirred at 60°C and 5000 r / min for 10 minutes, and then deionized water was dripped into the mixture at a rate of 160 ml / min. The dripping was stopped when the solid content reached 55%, and a water-based epoxy emulsion was obtained;
[0055] (4) Weigh 0.03 parts of a wetting and dispersing agent, 80 parts of a functionalized polysiloxane, 0.03 parts of a defoaming agent, 0.004 parts of azobisisobutyronitrile and 100 parts of deionized water and mix them evenly to obtain component A; the water-based epoxy emulsion is component B; and component A and component B are mixed at a mass ratio of 1:0.9 to obtain a quick-drying water-based epoxy coating.
[0056] Comparative Example 3:
[0057] A method for preparing a quick-drying waterborne epoxy coating comprises the following preparation steps:
[0058] (1) Tetramethylcyclotetrasiloxane, 4-(2-allyl)-catechol, and chloroplatinic acid were mixed in a mass ratio of 1:0.5:0.003, reacted at 85°C for 6 hours, and cooled to room temperature to obtain phenolic hydroxyl-modified cyclotetrasiloxane; phenolic hydroxyl-modified cyclotetrasiloxane and methyl propylene isocyanate were mixed in a mass ratio of 1:0.7, stirred at 75°C at 150 r / min for 5 hours to obtain modified cyclotetrasiloxane;
[0059] (2) Modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:0.6:0.6:0.02, nitrogen was passed for 15 minutes, and the mixture was stirred at 85°C and 150 r / min for 2.5 hours. Methoxytrimethylsilane (0.3 times the mass of tetramethylcyclotetrasiloxane) was added, the temperature was raised to 100°C and stirring was continued for 8 hours. The temperature was raised to 135°C at 15°C / min and stirring was continued for 45 minutes. The mixture was distilled at 0.2 MPa for 1.5 hours to obtain functionalized polysiloxane.
[0060] (3) Graphene oxide and deionized water were mixed at a mass ratio of 1:200, and ultrasonicated for 30 minutes to obtain a graphene oxide suspension. The graphene oxide suspension and ethylenediamine were mixed at a mass ratio of 1:7.5, stirred at 70°C at a speed of 70 r / min for 2 hours, and the solid product was centrifuged to obtain the solid product, which was washed 4 times with deionized water and freeze-dried for 48 hours to obtain the primary modified graphene; the primary modified graphene oxide, ethylenediamine, allylphosphine dichloride, triethylamine, and toluene were mixed at a mass ratio of 1:0.5:0.7:0.15:25, stirred at 2.5°C at 300 r / min for 3 hours, filtered, and the filter residue was washed 4 times with deionized water, and then immersed in a 25% mass concentration ethylenediamine ethanol solution for 2 hours, filtered, and the filter residue was washed 4 times with deionized water and anhydrous ethanol, respectively, and freeze-dried for 48 hours to obtain modified graphene;
[0061] (4) Diallyl bisphenol A diglycidyl ether and polyethylene glycol were mixed in a mass ratio of 1:10 and heated at 100°C for 30 minutes, and then the temperature was raised to 180°C, potassium persulfate was added in an amount of 0.0003 times the mass of diallyl bisphenol A diglycidyl ether, and the mixture was stirred at 300 r / min for 4 hours to obtain an emulsifier; Diallyl bisphenol A diglycidyl ether, OP-10, and emulsifier were mixed in a mass ratio of 1:0.03:0.07, and the mixture was stirred at 5000 r / min for 10 minutes at 60°C, and then deionized water was added dropwise at a rate of 160 ml / min. The addition was stopped when the solid content reached 55%, and a water-based epoxy emulsion was obtained;
[0062] (5) Weigh 1.5 parts of modified graphene, 0.03 parts of wetting and dispersing agent, 80 parts of functionalized polysiloxane, 0.03 parts of defoaming agent, 0.004 parts of azobisisobutyronitrile and 100 parts of deionized water and mix them evenly to obtain component A; the water-based epoxy emulsion is component B; and component A and component B are mixed at a mass ratio of 1:0.9 to obtain a quick-drying water-based epoxy coating.
[0063] Comparative Example 4:
[0064] A method for preparing a quick-drying waterborne epoxy coating comprises the following preparation steps:
[0065] (1) Tetramethylcyclotetrasiloxane, 4-(2-allyl)-catechol, and chloroplatinic acid were mixed in a mass ratio of 1:0.5:0.003, reacted at 85°C for 6 hours, and cooled to room temperature to obtain phenolic hydroxyl-modified cyclotetrasiloxane; N,N-dimethylaminopropyldimethylmethoxysilane and allyl chloride were mixed in a mass ratio of 1:0.8, stirred at 85°C at 400 r / min for 8 hours, and cooled to room temperature to obtain quaternary ammonium silane;
[0066] (2) Phenolic hydroxyl-modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 1:0.6:0.6:0.02, nitrogen was passed for 15 minutes, and the mixture was stirred at 85°C and 150 r / min for 2.5 hours. A quaternary ammonium silane with a mass of 0.3 times that of tetramethylcyclotetrasiloxane was added, the temperature was raised to 100°C and the stirring was continued for 8 hours. The temperature was raised to 135°C at 15°C / min and the stirring was continued for 45 minutes. The mixture was distilled at 0.2 MPa for 1.5 hours to obtain a functionalized polysiloxane.
[0067] (3) Graphene oxide and deionized water were mixed at a mass ratio of 1:200, and ultrasonicated for 30 minutes to obtain a graphene oxide suspension. The graphene oxide suspension and ethylenediamine were mixed at a mass ratio of 1:7.5, stirred at 70°C at a speed of 70 r / min for 2 hours, and the solid product was centrifuged to obtain the solid product, which was washed 4 times with deionized water and freeze-dried for 48 hours to obtain the primary modified graphene; the primary modified graphene oxide, ethylenediamine, allylphosphine dichloride, triethylamine, and toluene were mixed at a mass ratio of 1:0.5:0.7:0.15:25, stirred at 2.5°C at 300 r / min for 3 hours, filtered, and the filter residue was washed 4 times with deionized water, and then immersed in a 25% mass concentration ethylenediamine ethanol solution for 2 hours, filtered, and the filter residue was washed 4 times with deionized water and anhydrous ethanol, respectively, and freeze-dried for 48 hours to obtain modified graphene;
[0068] (4) Diallyl bisphenol A diglycidyl ether and polyethylene glycol were mixed in a mass ratio of 1:10 and heated at 100°C for 30 minutes, and then the temperature was raised to 180°C, potassium persulfate was added in an amount of 0.0003 times the mass of diallyl bisphenol A diglycidyl ether, and the mixture was stirred at 300 r / min for 4 hours to obtain an emulsifier; Diallyl bisphenol A diglycidyl ether, OP-10, and emulsifier were mixed in a mass ratio of 1:0.03:0.07, and the mixture was stirred at 5000 r / min for 10 minutes at 60°C, and then deionized water was added dropwise at a rate of 160 ml / min. The addition was stopped when the solid content reached 55%, and a water-based epoxy emulsion was obtained;
[0069] (5) Weigh 1.5 parts of modified graphene, 0.03 parts of wetting and dispersing agent, 80 parts of functionalized polysiloxane, 0.03 parts of defoaming agent, 0.004 parts of azobisisobutyronitrile and 100 parts of deionized water and mix them evenly to obtain component A; the water-based epoxy emulsion is component B; and component A and component B are mixed at a mass ratio of 1:0.9 to obtain a quick-drying water-based epoxy coating.
[0070] Comparative Example 5:
[0071] A method for preparing a quick-drying waterborne epoxy coating comprises the following preparation steps:
[0072] (1) N,N-dimethylaminopropyldimethylmethoxysilane and allyl chloride were mixed in a mass ratio of 1:0.8, stirred at 85°C and 400 r / min for 8 hours, and cooled to room temperature to obtain quaternary ammonium silane;
[0073] (2) 3-aminopropylmethyldimethoxysilane and tetramethylammonium hydroxide silicon alkoxide were mixed in a mass ratio of 0.6:0.6:0.02, nitrogen was passed through for 15 minutes, and stirred at 85°C and 150 r / min for 2.5 hours. A quaternary ammonium silane with a mass of 0.3 times that of tetramethylcyclotetrasiloxane was added, the temperature was raised to 100°C and stirring was continued for 8 hours, the temperature was raised to 135°C at 15°C / min and stirring was continued for 45 minutes, and distilled at 0.2 MPa for 1.5 hours to obtain a functionalized polysiloxane;
[0074] (3) Graphene oxide and deionized water were mixed at a mass ratio of 1:200, and ultrasonicated for 30 minutes to obtain a graphene oxide suspension. The graphene oxide suspension and ethylenediamine were mixed at a mass ratio of 1:7.5, stirred at 70°C at a speed of 70 r / min for 2 hours, and the solid product was centrifuged to obtain the solid product, which was washed 4 times with deionized water and freeze-dried for 48 hours to obtain the primary modified graphene; the primary modified graphene oxide, ethylenediamine, allylphosphine dichloride, triethylamine, and toluene were mixed at a mass ratio of 1:0.5:0.7:0.15:25, stirred at 2.5°C at 300 r / min for 3 hours, filtered, and the filter residue was washed 4 times with deionized water, and then immersed in a 25% mass concentration ethylenediamine ethanol solution for 2 hours, filtered, and the filter residue was washed 4 times with deionized water and anhydrous ethanol, respectively, and freeze-dried for 48 hours to obtain modified graphene;
[0075] (4) Diallyl bisphenol A diglycidyl ether and polyethylene glycol were mixed in a mass ratio of 1:10 and heated at 100°C for 30 minutes, and then the temperature was raised to 180°C, potassium persulfate was added in an amount of 0.0003 times the mass of diallyl bisphenol A diglycidyl ether, and the mixture was stirred at 300 r / min for 4 hours to obtain an emulsifier; Diallyl bisphenol A diglycidyl ether, OP-10, and emulsifier were mixed in a mass ratio of 1:0.03:0.07, and the mixture was stirred at 5000 r / min for 10 minutes at 60°C, and then deionized water was added dropwise at a rate of 160 ml / min. The addition was stopped when the solid content reached 55%, and a water-based epoxy emulsion was obtained;
[0076] (5) Weigh 1.5 parts of modified graphene, 0.03 parts of wetting and dispersing agent, 80 parts of functionalized polysiloxane, 0.03 parts of defoaming agent, 0.004 parts of azobisisobutyronitrile and 100 parts of deionized water and mix them evenly to obtain component A; the water-based epoxy emulsion is component B; and component A and component B are mixed at a mass ratio of 1:0.9 to obtain a quick-drying water-based epoxy coating.
[0077] Test Example 1:
[0078] Anticorrosion performance test: Apply quick-drying water-based epoxy coating to tinplate, seal the edges with transparent tape after drying, draw "X" on the coating surface, and then place the sample iron plate in a salt spray chamber for testing. The sample solution is 50g / L sodium chloride solution, the pH is adjusted to about 7, the test temperature is set to 35℃, and continuous spraying is used throughout the test period. The results are shown in Table 1.
[0079] Self-repairing performance: Apply quick-drying water-based epoxy coating to tinplate, seal the edges with transparent tape after drying, and draw an "X" on the surface of the coating. Heat the scratched sample iron plate at 130℃ for 30 minutes and then cool it to room temperature. Then place the sample iron plate in a salt spray chamber for testing. The sample solution is a 50g / L sodium chloride solution, the pH is adjusted to about 7, the test temperature is set to 35℃, and continuous spraying is used throughout the test cycle. The results are shown in Table 1.
[0080] Table 1
[0081] Rust condition Rust after heating Rust condition Rust after heating Example 1 No rust No rust Comparative Example 1 No rust No rust Example 2 No rust No rust Comparative Example 2 There is rust No rust Example 3 No rust No rust Comparative Example 3 No rust No rust Comparative Example 4 No rust There is rust Comparative Example 5 No rust There is rust
[0082] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the quick-drying waterborne epoxy coating prepared by the present invention has good anti-corrosion performance and self-repairing performance.
[0083] By comparison, the corrosion conditions of Examples 1 to 3 are better than those of Comparative Example 3, indicating that graphene oxide can play a role of physical barrier, and the amino groups and double bonds on the modified graphene oxide can form chemical crosslinks between graphene oxide and epoxy resin, making the coating structure tighter and effectively blocking the propagation of water and sodium salt ions, thereby improving the anti-corrosion performance of the quick-drying water-based epoxy coating.
[0084] By comparison, the rust conditions of Examples 1 to 3 after heating are better than those of Comparative Examples 4 and 5, indicating that the phenolic hydroxyl group on 4-(2-allyl)-catechol can block methyl methacrylate isocyanate, and heating after the quick-drying water-based epoxy coating is applied to the substrate to form a coating can deblock the isocyanate, and the isocyanate group reacts with the epoxy group to repair the coating surface, thereby improving the self-healing performance of the quick-drying water-based epoxy coating.
[0085] Test Example 2:
[0086] Hardness test method: Test pencil hardness according to GB / T6739, select tinplate substrate, apply each embodiment and comparative example coating on tinplate to form film, dry at 130℃ for 30min, sharpen the pencil until the lead core is exposed by 5-6mm, keep the cylindrical shape of the lead core, hold the pencil vertically and sandpaper at 90° to grind the lead core until a flat and smooth circular cross section is obtained, and there are no debris and gaps on the edge, fix the pencil on the pencil hardness tester and adjust the level, push at least 7mm at a speed of 0.5-1mm / s, and indicate the hardness of the paint film with the hardest pencil specification that does not scratch the paint film, and the pencil hardness has 13 levels from 6B to B, HB, H to 6H, among which 6B is the softest and 6H is the hardest. The results are shown in Table 2.
[0087] Table 2
[0088] hardness hardness Example 1 5H Comparative Example 1 4H Example 2 5H Comparative Example 2 2H Example 3 5H Comparative Example 3 3H Comparative Example 4 3H Comparative Example 5 2H
[0089] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the quick-drying waterborne epoxy coating prepared by the present invention has good hardness.
[0090] By comparison, the hardness of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that allylphosphine dichloride makes the surface of graphene oxide have double bonds, which can cross-link with the double bonds on diallyl bisphenol A diglycidyl ether and the functionalized polysiloxane under the action of azobisisobutyronitrile, thereby increasing the cross-linking density of the quick-drying water-based epoxy coating, thereby effectively increasing the hardness of the quick-drying water-based epoxy coating; the hardness of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that ethylenediamine successfully introduces amino groups on the surface of graphene oxide, which can cause the epoxy groups on diallyl bisphenol A diglycidyl ether to open the ring and cross-link, thereby increasing the cross-linking density and thus increasing the hardness of the quick-drying water-based epoxy coating; the hardness of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that N,N-dimethylaminopropyldimethylmethoxysilane and allyl chloride react to generate quaternized silane, introduce double bonds on the functionalized polysiloxane, and can cross-link with diallyl bisphenol A diglycidyl ether. The double bonds on the oil ether and the graphene oxide are cross-linked under the action of azobisisobutyronitrile, thereby increasing the cross-linking density of the quick-drying water-based epoxy coating, thereby effectively increasing the hardness of the quick-drying water-based epoxy coating; the hardness of Examples 1 to 3 is greater than that of Comparative Example 4, indicating that methyl methacrylate isocyanate reacts with phenolic hydroxyl-modified cyclotetrasiloxane to introduce double bonds on the functionalized polysiloxane, which can cross-link with the double bonds on diallyl bisphenol A diglycidyl ether and graphene oxide under the action of azobisisobutyronitrile, thereby increasing the cross-linking density of the quick-drying water-based epoxy coating, thereby effectively increasing the hardness of the quick-drying water-based epoxy coating; the hardness of Examples 1 to 3 is greater than that of Comparative Example 5, indicating that methyl methacrylate isocyanate will be unblocked at 130°C after being blocked by phenolic hydroxyl groups, and react with the epoxy groups on diallyl bisphenol A diglycidyl ether to increase the cross-linking density of the quick-drying water-based epoxy coating, thereby effectively increasing the hardness of the quick-drying water-based epoxy coating.
[0091] Test Example 3:
[0092] Antibacterial performance test: The materials of each embodiment and comparative example were crushed into powders of less than 150 microns, and the same mass was taken to test the antibacterial rate of the materials against Staphylococcus aureus according to the Quine test method. The results are shown in Table 3.
[0093] Table 3
[0094] Antibacterial rate (%) Antibacterial rate (%) Example 1 98.8 Comparative Example 1 98.2 Example 2 98.9 Comparative Example 2 9.3 Example 3 99.1 Comparative Example 3 98.7 Comparative Example 4 99.1 Comparative Example 5 98.8
[0095] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the quick-drying waterborne epoxy coating prepared by the present invention has good antibacterial properties.
[0096] By comparison, the antibacterial rates of Examples 1 to 3 are significantly greater than that of Comparative Example 2, indicating that N,N-dimethylaminopropyldimethylmethoxysilane and allyl chloride react to form quaternary ammonium salts to prepare quaternized silanes. Quaternary ammonium salts have good contact antibacterial effects as cationic antibacterial agents, thereby improving the antibacterial properties of quick-drying waterborne epoxy coatings.
[0097] Test Example 4:
[0098] Flame retardant performance test: The fast-drying waterborne epoxy coatings obtained in the embodiments and test examples were prepared into samples according to GB / T2406 and tested for limiting oxygen index. The results are shown in Table 4.
[0099] Table 4
[0100] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 36.2 Comparative Example 1 27.1 Example 2 36.1 Comparative Example 2 24.6 Example 3 36.4 Comparative Example 3 35.9 Comparative Example 4 36.2 Comparative Example 5 36.0
[0101] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 4, it can be found that the quick-drying waterborne epoxy coating prepared by the present invention has good flame retardant properties.
[0102] By comparison, the limiting oxygen index of Examples 1 to 3 is significantly greater than that of Comparative Example 4, indicating that allyl phosphine dichloride promotes the formation of a dense carbon layer on the surface of the coating, and the dense carbon layer can block heat and oxygen transfer, reduce combustion inside the material, and thus improve the flame retardant properties of the quick-drying waterborne epoxy coating; the limiting oxygen index of Examples 1 to 3 is significantly greater than that of Comparative Example 5, indicating that graphene oxide can play a barrier role in the combustion process, preventing the escape of combustible gases and heat, thereby effectively improving the flame retardant properties of the quick-drying waterborne epoxy coating.
[0103] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A quick-drying water-based epoxy coating, characterized in that: The quick-drying water-based epoxy coating is prepared by preparing component A from modified graphene, functionalized polysiloxane, a defoamer, azobisisobutyronitrile and deionized water, and mixing component A and component B with water-based epoxy emulsion; The functionalized polysiloxane is prepared by reacting modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and quaternized silane; The modified graphene is prepared by reacting graphene oxide with diethylamine, allylphosphine dichloride and triethylamine; The water-based epoxy emulsion is prepared by the reaction of diallyl bisphenol A diglycidyl ether, OP-10, an emulsifier and an emulsifier.
2. A method for preparing a quick-drying waterborne epoxy coating, characterized in that: The method comprises the following preparation steps: (1) Tetramethylcyclotetrasiloxane, 4-(2-allyl)-catechol, and chloroplatinic acid are mixed in a mass ratio of 1: (0.3-0.7): (0.002-0.004), reacted at 80-90°C for 5-7 hours, and cooled to room temperature to obtain phenolic hydroxyl-modified cyclotetrasiloxane; phenolic hydroxyl-modified cyclotetrasiloxane and methyl propylene isocyanate are mixed in a mass ratio of 1: (0.6-0.8), stirred at 70-80°C at 100-200 r / min for 4-6 hours to obtain modified cyclotetrasiloxane; N,N-dimethylaminopropyldimethylmethoxysilane and propylene chloride are mixed in a mass ratio of 1: (0.7-0.9), stirred at 80-90°C at 300-500 r / min for 6-10 hours, and cooled to room temperature to obtain quaternary ammonium silane; (2) Modified cyclotetrasiloxane, 3-aminopropylmethyldimethoxysilane and tetramethylammonium hydroxide silicon alkoxide are mixed in a mass ratio of 1: (0.5-0.7): (0.5-0.7): (0.01-0.03), nitrogen is passed through for 10-20 min, stirred at 100-200 r / min at 80-90° C. for 2-3 h, quaternary ammonium silane of 0.2-0.4 times the mass of tetramethylcyclotetrasiloxane is added, the temperature is raised to 95-105° C. and stirring is continued for 7-9 h, the temperature is raised to 130-140° C. at 10-20° C. / min and stirring is continued for 40-50 min, and distilled at 0.1-0.3 MPa for 1-2 h to obtain functionalized polysiloxane; (3) Graphene oxide and deionized water are mixed at a mass ratio of 1:(190-210), and ultrasonicated for 25-35 min to obtain a graphene oxide suspension. The graphene oxide suspension and ethylenediamine are mixed at a mass ratio of 1:(7-8), and stirred at 65-75° C. and a speed of 60-80 r / min for 1.5-2.5 h. The solid product is centrifuged and washed with deionized water for 3-5 times, and freeze-dried for 46-50 h to obtain primary modified graphene. The primary modified graphene oxide, ethylenediamine, and allyl dichloride are mixed. Phosphine, triethylamine and toluene are mixed in a mass ratio of 1: (0.4-0.6): (0.6-0.8): (0.1-0.2): (20-30), stirred at 200-400 r / min for 2-4 hours at 0-5°C, filtered, washed the filter residue with deionized water for 3-5 times, immersed in a 20%-30% mass concentration ethylenediamine ethanol solution for 1-3 hours, filtered, washed the filter residue with deionized water and anhydrous ethanol for 3-5 times respectively, and freeze-dried for 46-50 hours to obtain modified graphene; (4) diallyl bisphenol A diglycidyl ether and polyethylene glycol are mixed in a mass ratio of 1:(5-15) and heated at 100° C. for 30 min, and the temperature is raised to 175-185° C., potassium persulfate is added in an amount of 0.0002-0.0004 times the mass of diallyl bisphenol A diglycidyl ether, and the mixture is stirred at 250-350 r / min for 3-5 h to obtain an emulsifier; diallyl bisphenol A diglycidyl ether, OP-10, and an emulsifier are mixed in a mass ratio of 1:(0.02-0.04):(0.06-0.08), and the mixture is stirred at 4500-5500 r / min for 5-15 min at 55-65° C., and deionized water is added dropwise at a rate of 160 ml / min. The addition of the dropwise addition is stopped when the solid content reaches 50%-60%, to obtain an aqueous epoxy emulsion; (5) Weigh 1 to 2 parts of modified graphene, 0.025 to 0.035 parts of wetting and dispersing agent, 75 to 85 parts of functionalized polysiloxane, 0.025 to 0.035 parts of defoaming agent, 0.003 to 0.005 parts of azobisisobutyronitrile and 90 to 110 parts of deionized water and mix them evenly to obtain component A; the water-based epoxy emulsion is component B; and component A and component B are mixed at a mass ratio of 1:(0.8 to 1) to obtain a quick-drying water-based epoxy coating.
3. The method for preparing a quick-drying waterborne epoxy coating according to claim 2, characterized in that: The graphene oxide described in step (3) is graphene oxide with a purity of 96%.
4. The method for preparing a quick-drying waterborne epoxy coating according to claim 2, characterized in that: The polyethylene glycol described in step (4) is polyethylene glycol with an average molecular weight of 4000.
5. The method for preparing a quick-drying waterborne epoxy coating according to claim 2, characterized in that: The wetting dispersant described in step (5) is a YL-190 type dispersant; and the defoaming agent is an AKN-3386 type defoaming agent.
Citation Information
Cited By
Acid and alkali resistant and salt spray resistant coating and preparation method thereof
CN120365850A